Association between ACTN3 (R577X), ACE (I/D), BDKRB2 (-9/+9), and AGT (M268T) polymorphisms and performance phenotypes in Brazilian swimmers - Severino Leão de Albuquerque-Neto; Marcos Antonio Pereira dos Santos; Valmir Oliveira Silvino; Jose Juan Blanco Herrera; Thiago Santos Rosa; Glauber Castelo Branco Silva; Bruno Pena Couto; Cirley Pinheiro Ferreira; Alexandre Sérgio Silva; Sandro Soares de Almeida; Gislane Ferreira de Melo (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background The influence of genetic polymorphisms on athletic performance has been widely explored. This study investigated the interactions between the polymorphisms ACTN3 (R577X), ACE (I/D), BDKRB2 (-9/+9), and AGT (M/T) and their association with endurance and strength phenotypes in Brazilian swimmers. Methods 123 athletes (aged 20–30 years) and 718 controls participated in the study. The athletes were divided into elite and sub-elite (N = 19 and 104, respectively) and strength and endurance experts (N = 98 and 25, respectively). Hardy-Weinberg equilibrium was observed in all groups. Results Considering the ACE polymorphism, it was observed a higher frequency of the DD genotype than expected in the strength experts of the elite group, whereas the strength experts sub-elite athletes had a higher frequency of the ID genotype (χ2 = 8.17; p = 0.01). Subjects with XX genotypes of ACTN3 are more likely to belong to the athlete group when compared to the control group (OR = 1.79, p = 0.04). The DD homozygotes of the ACE are more likely to belong to the elite group with strength phenotypes than the group of sub-elite (OR = 7.96, p = 0.01) and elite strength experts compared to elite endurance (OR = 18.0, p = 0.03). However, no significant differences were observed in the allelic distribution of the polymorphisms evaluated when comparing Elite, sub-elite athletes and controls. Conclusion ACE and ACTN3 allele frequencies should be considered with regard to performance influencing factors in Brazilian swimmers.